Differences in Postpartum Depression and Breast Milk Production in Postpartum Mothers After Implementing Postnatal Yoga - Septiana Wulandari; Erna Rahma Yani; Finta Isti Kundarti (EMBRIO: Jurnal Kebidanan, 2024)
Breastfeeding is an important event for women that involves physical and psychosocial changes. One form of physical activity is yoga. Yoga is a type of exercise that is done during the postpartum period. It is hoped that it can help mothers improve their mental health, relax, stabilize their emotions, and be more confident in facing their new role as mothers.  This research aims to determine the differences in postpartum depression and breast milk production in postpartum mothers after implementing postnatal yoga. The method in this research is a quasi-experiment with a pretest-posttest control group design. The sample size in this study was 32: 16 control and 16 intervention groups. The sampling technique uses a random sampling technique. The results of the paired sample T-test on postpartum depression during the pretest-posttest in the intervention group showed significant results, namely a p-value of 0.004 (p-value  less than 0.05). Meanwhile, breast milk production in the intervention group showed significant results, namely a p-value of 0.000 (p-value less than 0.05). In the control group, postpartum depression showed a p-value of 0.090 (p-value more than 0.05), while breast milk production showed a p-value of 0.110 (p-value more than 0.05). The conclusion is that there are differences in postpartum depression and breast milk production in postpartum mothers after implementing postnatal yoga.